1988
DOI: 10.1073/pnas.85.23.9209
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD3-associated antigen-binding receptors on suppressor T cells.

Abstract: Three suppressor T (Ts)-cell hybridomas specific for 4-hydroxy-3-nitrophenyl acetyl (NP) hapten were selected for surface expression of cluster determinant 3 (CD3) by using antibody (anti-CD3) or antigen (NP-bovine serum albumin) panning procedures followed by cloning at limiting dilution. The CD3-selected Ts hybridomas showed a 1-2 logarithmic enrichment in suppressor activity when compared to the parent lines; they also specifically bound NP-coupled sheep red blood cells in rosette assays. This antigen-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Utilizing the strategies of TcR a or p expression loss variants followed by reconstitution with homologous TcR a cDNA, a critical role for TcR a chain in antigen-specific Ts function was directly demonstrated. (11). This observation has been confirmed in other suppressor T-cell systems (12,24,25).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Utilizing the strategies of TcR a or p expression loss variants followed by reconstitution with homologous TcR a cDNA, a critical role for TcR a chain in antigen-specific Ts function was directly demonstrated. (11). This observation has been confirmed in other suppressor T-cell systems (12,24,25).…”
Section: Discussionsupporting
confidence: 72%
“…Initially, donorderived TcR (3-chain rearrangements were not detected in antigen-specific suppressor T-cell (Ts) hybridomas (1,2). Subsequent analyses of Ts hybridomas indicated that Ts do express TcR a-chain mRNA derived from the Ts donor (3,4) and that some express the CD3-TcR a/(3 complex on their surface (5)(6)(7)(8)(9)(10)(11). Selection of Ts hybridomas for expression of surface CD3 resulted in an increase in antigen binding (11) and suppressive bioactivity (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the earlier results on the absence of TCR in regulatory T-cell hybridomas must be reevaluated. More recently, Kuchroo et al (25) confirmed and extended these findings by using several Ts3 hybridomas. Selection for CD3' cells resulted in enhanced factor production and yielded populations capable of binding antigen.…”
Section: Discussionsupporting
confidence: 67%
“…In order to assess the blocking effect of TNP-lysine on specif ic Ag binding by immune LN cells, we utilized a rosette as say [15,16]. TNCB-immune LN cells were incubated for 1 h at 4°C with different concentrations of TNP-lysine in Hank's balanced salt solution (HBSS) (Nissui Pharmaceu tical Co.).…”
Section: Binding Ability O F Tnp-lysine To T-cell Receptorsmentioning
confidence: 99%